62+52=c2

Rewrite the equation as c2=62+52.

c2=62+52

Take the square root of both sides of the equation to eliminate the exponent on the left side.

c=±62+52

Simplify the right side of the equation.

Raise 6 to the power of 2.

c=±36+52

Raise 5 to the power of 2.

c=±36+25

Add 36 and 25.

c=±61

c=±61

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

c=61

Next, use the negative value of the ± to find the second solution.

c=-61

The complete solution is the result of both the positive and negative portions of the solution.

c=61,-61

c=61,-61

c=61,-61

The result can be shown in multiple forms.

Exact Form:

c=61,-61

Decimal Form:

c=7.81024967…,-7.81024967…

Solve for c 6^2+5^2=c^2